Impacts and Challenges of ICT Based Scale-up Campaigns: Lessons Learnt from the Use of SMS to Support Maize Farmers in the UPTAKE Project, Tanzania. (26th February 2020) - Karanja, Lucy; Gakuo, Stephanie; Kansiime, Monica; Romney, Dannie; Mibei, Henry; Watiti, James; Sabula, Leonard; Karanja, Daniel
Providing smallholder farmers with support through conventional government extension approaches is challenging as the number of extension agents is decreasing. At the same time, new information and communication technologies (ICTs), such as short message services (SMS) sent via mobile phones, show considerable promise to complement existing extension services. In the UP-scaling Technology in Agriculture through Knowledge and Extension (UPTAKE) Project, ICTs were used to create awareness and increase uptake and adoption of agricultural innovations by maize farmers in Tanzania. Two SMS-based maize campaigns were implemented during the 2016/2017 and 2017/2018 cropping seasons in the Southern Highlands of Tanzania. Prior to the start of the campaigns, formative research to determine maize production knowledge, practices and challenges was conducted in Mbeya and Songwe Region. After the campaign a telephone survey, key informant interviews and focus group discussions were conducted. During the campaign, about 3.8 million SMS were disseminated to over 55, 000 farmers. 73% were male, 19% owned smart phones and 86% farmed maize on up to 1.2 hectares of land. Farmers reported maize production challenges as: unreliable markets, inadequate extension services, pest outbreaks and lack of knowledge to identify counterfeit inputs particularly seeds and fertilizers. The UPTAKE mobile SMS campaign was a new approach to agricultural extension in this area. A telephone survey amongst a sample of farmers who received the SMS revealed that 53% of respondents considered that this was now their preferred as a source of information compared to traditional sources including neighbours and family members, demonstration plots, agricultural extension workers and radios. Key lessons learnt relate to management of databases of farmer contacts, importance of participatory processes in developing content and designing SMS campaigns, and the need for flexibility and promptness in responding to emerging threats such as delayed rains and outbreaks of pests. Good practices like buy in and authorizations from the government administrative structures and compliance with country's regulations on communication are integral to the success of ICT projects.